Lean body mass, muscle architecture, and performance in well-trained female weightlifters - Zaras, N.; Stasinaki, A.-N.; Spiliopoulou, P.; Hadjicharalambous, M.; Terzis, G. (Sports, 2020)
Lean mass and quadriceps muscle architecture have been associated with performance in male well-trained weightlifters, but no data exist for female weightlifters. The aim of the study is to investigate the relationship between lean mass, quadriceps cross sectional area (CSA), and muscle architecture with weightlifting performance in female weightlifters. Eight well-trained female weightlifters (age 23.5 ± 6.3 years, maximum total lifting performance = 147.4 ± 34.1 kg) participated in the study. Five of the athletes were members of the national team and three were among the nation`s top-five performers of the respective body-weight category. Measurements included maximum lifting performance in snatch and clean and jerk, body composition (dual x-ray absorptiometry), vastus lateralis (VL) muscle architecture, vastus intermedius (VI) muscle thickness and quadriceps muscles` CSA and countermovement jump (CMJ). Very large to nearly perfect correlations were found between snatch and clean and jerk for trunk lean body mass (r = 0.959 and 0.929), for total CSA (r = 0.732 and 0.608), and CMJ power (r = 0.933 and 0.896). These results suggest that lean body mass, quadriceps` CSA and CMJ should be monitored regularly in female weightlifters to detect potential modifications in lifting performance.